1995
DOI: 10.1111/j.2042-3306.1995.tb04937.x
|View full text |Cite
|
Sign up to set email alerts
|

Sweat composition: comparison of collection methods and effects of exercise intensity

Abstract: SummaryThe objectives of this study were to compare sweat collection techniques and determine effect of low and high intensity exercise on the composition and osmolality of equine sweat in exercise trained Thoroughbred horses. Sweat collection sites included the neck and thorax, bilaterally and behind the girth ventrally. Sweat was collected in cotton gauze, either exposed to the air or contained within a plastic pouch, from sealed pouches, with or without application of vaseline to the skin, and as it dripped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 20 publications
2
23
1
Order By: Relevance
“…Since equine sweat is rich in sodium, potassium and chloride [3], [4], [5], [6], [7], [8], diets marginal in these electrolytes may cause disturbances of fluid and mineral homeostasis and therefore potentially health problems in exercised horses [9]. However, recently the value of supplementing, especially in the non-endurance horse, at the currently recommended levels has been questioned and this topic has become highly controversial [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since equine sweat is rich in sodium, potassium and chloride [3], [4], [5], [6], [7], [8], diets marginal in these electrolytes may cause disturbances of fluid and mineral homeostasis and therefore potentially health problems in exercised horses [9]. However, recently the value of supplementing, especially in the non-endurance horse, at the currently recommended levels has been questioned and this topic has become highly controversial [10].…”
Section: Introductionmentioning
confidence: 99%
“…Spooner et al [18] observed a comparatively low sodium content in the sweat of Arabian horses. Evaporation of water during sweat collection may lead to an overestimate of the electrolyte content of sweat [5]. In addition, sweat losses show considerable variation, and they are not very closely linked to the intensity of work but also to other factors such as environmental temperature and individual horse [19].…”
Section: Introductionmentioning
confidence: 99%
“…1995b). Comparing Ca and Mg to values reported by McCutcheon et al . (1995b), Ca values obtained here are greater (6.6–12 mmol/l vs. 4.8 mmol/l), while Mg is quite similar (1.6–3.3 mmol/l vs. 3.3 mmol/l).…”
Section: Discussionmentioning
confidence: 76%
“…Comparing the sweat concentrations of Na, K, and Cl to those previously reported (Table 3), the Na concentration we observed (88–104 mmol/l depending on diet) in this study was clearly lower than the previously reported range (range 110–249). This may be the result of a difference in collection method, as some of the previous studies technique may have allowed sweat to evaporate which would have falsely increased the concentrations reported (McCutcheon et al . 1995b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation